Innovation happens elsewhere open source as business strategy - Goldman, Ron, 1952-; Gabriel, Richard P. (Amsterdam ; Boston : Morgan Kaufmann, 2005)
It's a plain fact: regardless of how smart, creative, and innovative your organization is, there are more smart, creative, and innovative people outside your organization than inside. Open source offers the possibility of bringing more innovation into your business by building a creative community that reaches beyond the barriers of the business. The key is developing a web-driven community where new types of collaboration and creativity can flourish. Since 1998 Ron Goldman and Richard Gabriel have been helping groups at Sun Microsystems understand open source and advising them on how to build successful communities around open source projects. In this book the authors present lessons learned from their own experiences with open source, as well as those from other well-known projects such as Linux, Apache, and Mozilla. * Winner of 2006 Jolt Productivity Award for General Books * Describes how open source development works and offers persuasive reasons for using it to help achieve business goals. * Shows how to use open source in day-to-day work, discusses the various licenses in use, and describes what makes for a successful project. * Written in an engaging style for executives, managers, and engineers that addresses the human and business issues involved in open source development as well as its history, philosophy, and future.
Innovation happens elsewhere -- What is open source? -- Why consider open source? -- Licenses -- How to do open-source development -- Going with open source -- How to build momentum -- What to avoid : known problems and failures.
Includes bibliographical references (p. 383-385) and index.
Keywords: Open source software; Business -- Computer programs; Electronic books